Efforts of the Office of Religious Affairs in Reducing Underage Marriage Rates - Ramadhani S, Sufina Anugerah; Junus, Nirwan; Meiske Kamba, Sri Nanang (Universitas Negeri Gorontalo, 2025)
Abstract: This study aims to examine the role of the Office of Religious Affairs (Kantor Urusan Agama or KUA) in reducing underage marriage rates and to identify the factors that hinder the execution of its duties. The research employs a qualitative approach with a descriptive method. Primary data were collected through in-depth interviews with KUA officials, community leaders, parents, and underage marriage participants, while secondary data were gathered from official documents, annual reports, and relevant literature. The findings reveal that KUA has implemented various measures to prevent early marriages, such as stringent administrative document verification, community outreach, and premarital counseling. However, KUA faces several challenges, including limited human resources, cultural resistance, and a lack of cross-sectoral collaboration, which hinder its effectiveness in combating underage marriages. This study recommends strengthening institutional capacity, enhancing cross-sectoral collaboration, and leveraging digital technology to support education and prevention efforts. With a holistic strategy and strong support from various stakeholders, underage marriage rates can be significantly reduced.